Utility of Combination Antimicrobial Therapy in Adults with Bloodstream Infections due to Enterobacteriaceae and Non-Fermenting Gram-Negative Bacilli Based on In Vitro Analysis at Two Community Hospitals - Rachel A. Foster; Casey Troficanto; P. Brandon Bookstaver; Joseph Kohn; Julie Ann Justo; Majdi N. Al-Hasan (MDPI AG, 2019)
This study examined the utility of combination therapy for bloodstream isolates of Enterobacteriaceae and non-fermenting Gram-negative bacilli (NFGN) from adults at two community hospitals from January 2010 through to June 2015. Changes to in vitro antimicrobial susceptibilities by adding ciprofloxacin or gentamicin to third-generation cephalosporins (3GC) were examined overall and in patients with risk factors for 3GC resistance. Overall ceftriaxone susceptibility among Enterobacteriaceae was 996/1063 (94%) and 247/295 (84%) in patients with 3GC resistance risk factors. Susceptibilities increased marginally by adding ciprofloxacin or gentamicin (mean difference 2.4% (95% CI 1.5, 3.4) and 3.0% (95% CI 2.0, 4.0), respectively, overall and 5.4% (95% CI 2.8, 8.0) and 7.1% (95% CI 4.2, 10.1), respectively, in patients with risk factors). Eighty-three of 105 (79%) NFGN were susceptible to ceftazidime overall and 20/29 (69%) in patients with prior beta-lactam use. Overall mean increase in susceptibilities was 15.2% (95% CI: 8.3, 22.2) and 17.1% (95% CI: 9.8, 24.5) for ciprofloxacin and gentamicin combinations, respectively; and 27.6% (95% CI: 10.3, 44.9) for either one with recent beta-lactam use. In this setting, empirical combination therapy had limited utility for Enterobacteriaceae bloodstream isolates but provided significant additional antimicrobial coverage to ceftazidime for NFGN, particularly in patients with prior beta-lactam use.